Electronic nicotine delivery system (ENDS) liquid nicotine exposure in young children presenting to US emergency departments, 2018 - Joanne T. Chang; Brian L. Rostron (BMC, 2019)
Abstract Background Increased use of electronic nicotine delivery systems (ENDS) in the United States (U.S.) has been related to acute adverse events from liquid nicotine exposure. Previous studies have reported on these events through 2017. Findings We used 2018 National Emergency Injury Surveillance System data to generate national estimates with 95% confidence intervals (CIs) of ENDS liquid nicotine-related poisonings among children under age 5 treated in U.S. hospital emergency departments (EDs). In 2018, an estimated 885 (95% CI: 397-1374) poisoning cases related to liquid nicotine among children under 5 were treated in U.S. EDs, which was a non-statistically signficant increase from 2017 (411 poisoning cases, 95% CI: 84-738). The most common route of exposure was through ingestion (99.4%). The majority of cases were treated and released from the hospital (90.0%), 8.9% of the cases left the hospital without being seen, and 1.1% of the cases were treated and admitted to the hospital. Conclusions This study provides updated national estimates of poisoning events related to liquid nicotine exposure that occurred in 2018 among children under age 5. Updated information from this study may complement public education efforts and prevent liquid nicotine exposure among children.